Pasture Access Affects Behavioral Indicators of Wellbeing in Dairy Cows - Andrew Crump; Kirsty Jenkins; Emily J. Bethell; Conrad P. Ferris; Gareth Arnott (Animals, 2019)
Dairy cows are increasingly housed indoors, either year-round or for long stretches over the winter and around parturition. This may create health and welfare issues. In cattle, lying and walking are highly motivated, and herds synchronize lying behavior when they have comfortable surfaces and little competition for space. Lying and walking activity can, therefore, indicate good welfare. Using a repeated measures crossover design, we gave 29 Holstein−Friesian dairy cows 18 days of overnight pasture access (PAS treatment) and 18 days of indoor housing (PEN treatment). Accelerometers recorded their lying and locomotory behavior. We measured behavioral synchrony with Fleiss’ Kappa and analyzed the accelerometry data using linear mixed models. Compared to the PEN treatment, the PAS treatment had longer overnight lying durations (χ21 = 27.51, p < 0.001), fewer lying bouts (χ21 = 22.53, p < 0.001), longer lying bouts (χ21 = 25.53, p < 0.001), and fewer transitions up or down (χ21 = 16.83, p < 0.001). Herd lying behavior was also more synchronous at pasture (χ21 = 230.25, p < 0.001). In addition, nightly step counts were higher in the PAS treatment than the PEN treatment (χ21 = 2946.31, p < 0.001). These results suggest pasture access improves dairy cow welfare by increasing comfort, reducing competition and boredom, and facilitating motivated behavior.